Review of Utilization, Chemical Content, and Pharmacological Activity of Macroalgaes for Development and Empowerment of Natural Resources on South Garut, Indonesia - Nur Amalia; Fauzia Noprima Okta; Aliya Azkia Zahra; Noviyanti Noviyanti; Aji Najihudin; Doni Anshar Nuari (Faculty of Mathematic and Natural Science, Garut University, 2026)
Macroalgae are autotrophic organisms that lack organs typically found in plants, such as roots, stems, and leaves. Macroalgae are grouped based on shape, size, and color. One of the coastal areas with abundant natural resources is the Garut Regency, Indonesia. This review aims to provide an updated assessment of the utilization, chemical composition, and pharmacological activities of macroalgae, to develop macroalgae as a natural resource. An updated review of macroalgae's utilization, chemical content, and pharmacological activities for developing and empowering macroalgae as natural resources in South Garut, Indonesia. This article was written by reviewing scientific articles published in the last 10 years on the utilization, chemical content, and pharmacological activities of macroalgae. In the coastal areas of Garut Regency, 44 species of macroalgae are found, comprising three divisions: Chlorophyta, Phaeophyta, and Rhodophyta. Macroalgae have benefited from an ecological and economic perspective. The chemical content of macroalgae can also be utilized as raw materials or additional ingredients in various industries, including the food, supplement, pharmaceutical, agricultural, and cosmetics industries. The bioactive compound content of each type of macroalgae can vary. Sargassum sp. contains bioactive compounds such as alkaloids, flavonoids, tannins, terpenoids, phenolics, saponins, steroids, glycosides, and chlorophyll. Glacilaria sp. contains bioactive compounds such as phenolic compounds, triterpenoids, flavonoids, and fatty acids. Ulva lactuca contains flavonoids, alkaloids, tannins, triterpenoids, saponins, catechins, quercetin, rutin, campherol, caffeic acid, ellagic acid, and chlorogenic acid. The influence of seasons and variations in harvest will influence the chemical content in macroalgae. Macroalgae possess several pharmacological properties, including antioxidant, antibacterial, anti-inflammatory, and anticancer effects. Various industries can utilize Macroalgae in the coastal waters of South Garut because they are rich in phytochemical content and pharmacological activity, making them suitable for the development and sustainable use of natural resources essential for human life.